2020
DOI: 10.1021/jacs.0c01429
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Distance Dependence for Proton-Coupled Tyrosine Oxidation in Oligoproline Peptides

Abstract: We have explored the kinetic effect of increasing electron transfer distance in a biomimetic, proton coupled electron transfer system (PCET). Biological electron transfer is often simultaneous with proton transfer in order to avoid the high-energy, charged intermediates resulting from the stepwise transfer of protons and electrons. These concerted proton electron transfer (CPET) reactions are implicated in numerous biological electron transfer pathways. In many cases, proton transfer is coupled to long-range e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 106 publications
(289 reference statements)
1
11
0
Order By: Relevance
“…The relatively flat curve for ln­[ k PCET ( R ET )] versus R ET in Figure C at small R ET predicts similar rate constants for the PCET systems with no proline linkage and with a single proline linkage, assuming the same value for V el 0 . This behavior is consistent with experimental data indicating that the PCET system without a proline linkage has a rate constant of 3 × 10 6 M –1 s –1 , which is similar to the rate constant of 1.4 × 10 6 M –1 s –1 measured experimentally for the PCET system with one proline linkage. As mentioned in the Introduction, only a few studies of the dependence of the PCET rate constant on the ET distance have been reported. ,, In the study of PCET in iron carboxy­tetraphenyl­porphyrin complexes, a relatively small slope magnitude of 0.23 Å –1 for the distance dependence of the rate constant was measured, compared to the value of 0.4–0.46 Å –1 measured for ET reactions with the same bridge unit. , In this system, the PCET reaction has an electrostatic term with Δ­( Q Ru Q PA ) = e 2 , while each ET reaction has an electrostatic term with Δ­( Q Ru Q PA ) = − e 2 or zero.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The relatively flat curve for ln­[ k PCET ( R ET )] versus R ET in Figure C at small R ET predicts similar rate constants for the PCET systems with no proline linkage and with a single proline linkage, assuming the same value for V el 0 . This behavior is consistent with experimental data indicating that the PCET system without a proline linkage has a rate constant of 3 × 10 6 M –1 s –1 , which is similar to the rate constant of 1.4 × 10 6 M –1 s –1 measured experimentally for the PCET system with one proline linkage. As mentioned in the Introduction, only a few studies of the dependence of the PCET rate constant on the ET distance have been reported. ,, In the study of PCET in iron carboxy­tetraphenyl­porphyrin complexes, a relatively small slope magnitude of 0.23 Å –1 for the distance dependence of the rate constant was measured, compared to the value of 0.4–0.46 Å –1 measured for ET reactions with the same bridge unit. , In this system, the PCET reaction has an electrostatic term with Δ­( Q Ru Q PA ) = e 2 , while each ET reaction has an electrostatic term with Δ­( Q Ru Q PA ) = − e 2 or zero.…”
Section: Resultssupporting
confidence: 91%
“…Impact of Coupling Attenuation Parameter. Previous work 50 suggested that the coupling attenuation parameter β ET may be different for the ET and PCET systems, based on the different donor−bridge−acceptor energetics. To investigate this possibility, we repeated our calculations with β ET = 1.2 Å −1 rather than 1.4 Å −1 for the PCET systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations